Degradation of PFOS and PFOA in soil and groundwater samples by high dose Electron Beam Technology. (December 2021) - Lassalle, John; Gao, Ruilian; Rodi, Robert; Kowald, Corinne; Feng, Mingbao; Sharma, Virender K.; Hoelen, Thomas; Bireta, Paul; Houtz, Erika F.; Staack, David; Pillai, Suresh D.
Abstract: Remediation technologies are urgently needed to degrade poly – and per fluoroalkyl substances (PFAS) in groundwater and soils. Since high energy electron beam (eBeam) technology involves rapid oxidation and reduction reactions it has the potential to breakdown PFAS. In this study, the technology was applied to PFAS-contaminated groundwater and soil samples to degrade PFOS and PFOA and other PFAS. An eBeam dose of 2000 kGy (kGy) reduced PFOS and PFOA concentrations in groundwater by 87.9% and 53.7% respectively. In soils with 10% moisture content, PFOS and PFOA concentrations were reduced by 99.9% and 86.5%, respectively. Out of 17 different PFAS that were detected in the soil sample, the 2000 kGy dose was able to degrade 10 PFAS to below detectable levels: PFNA (initially 19.4 ng/g), PFDA (3.9 ng/g), PFPeS (12.1 ng/g), PFHxS (365 ng/g), PFHpS (18.0 ng/g), PFNS (4.3 ng/g), 4:2 FTS (16.6 ng/g), 6:2 FTS (146.1 ng/g), 8:2 FTS (165.6 ng/g) and PFOSA (171.8 ng/g). Of the remaining 7 PFAS, the removal efficiency ranged between 49% and 99.9%. It appears that eBeam degradation of PFAS in soil is more effective at reduced soil moisture content. Highlights: Remediation technologies needed for PFAS-contaminated soil and ground water. 2000 kGy eBeam dose achieved significant PFAS removal in soil and water. Temperature increase associated with high doses involved in PFAS degradation. Reduced soil moisture enhances PFAS remediation.